Optimal storage conditions for the detection of enolase derived from the midguts of field collected Aedes albopictus / Nurul Izni Rosman - Rosman, Nurul Izni (2015)
Dengue virus (DENV), is an arbovirus vectored by Aedes albopictus, has high tolerance in adapting to new environment including in vector and human cells. The ability of the virus to interact successfully with the protein receptor on the mosquito midgut epithelial cells contributes to the transmission of this virus to human. One of the proteins involve is enolase, which can activate plasminogen in the body leading to dengue hemorrhagic fever. In order to reduce the dengue fever cases, studies of immunology and proteomic regarding DENV need to be done for the objective to be achieved. However, improper sample collection, transportation and handling might cause the sample degraded and resampling during outbreak season pose risk to researcher. This study aim to determine the optimum media and the best storage conditions for midgut tissues of field collected Ae. albopictus by SDS-PAGE analysis. Samples ofAe. albopictus collected from Kolej A5, UiTM Puncak Alam were reared and adult mosquito were dissected to obtain the midgut tissues. The tissues were then preserved in phosphate buffered saline (PBS), normal saline, distilled water and 1X TAE Buffer for a week at room temperature, 4°C and 20° C. SDS-PAGE was done after a week and the result showed no expected bands at molecular weight of 57 and 67 kDa were revealed from the preserved sample. This result shows that the midgut tissues are not suitable for preservation purposes and further experiment involving protein sequencing and affinity chromatography may be used to substantiate findings.